The Components Which Affect the Adoption Of E-Government Applications in Jordan - Al Zoubi, Mohmmad Issa (International Journal of Advanced Science and Technology, 2019)
The goal of the following paper will be to analyze the reasons which affect the adoption of citizens in Jordan of the e-government. The model of research was improved relying on the collaboration of the diffusion of innovative and technological approved model in addition to the examination of the mediating effect of perceived usefulness and perceived trust on the relationships among the adoption of e-government in Jordan and perceived ease of use. In order to examine the relationships which are empirically hypothesized among numerals a replica consisting of the variables mentioned earlier was improved relying on the review of literature. Utilizing AMOS program 22 and using Structural Equation Modeling (SEM), this model was analyzed. A descriptive, quantitative explanation of a self-administered built questionnaire which was created to analyze the relationships of models and distributed on. The information was gathered using a questionnaire of Likert-scale from poor, urban citizens 416 who are Jordanian. Empirical resolutions show that Image had a greatly positive effect on adopting e-governments, perceiving usefulness and adopting e-government findings also revealed that perceived trust impacts greatly on the perceived ease of utilization and the adoption of e-government in Jordan. The outcomes can be helpful for the companies to improve their service for their consumers by the strategies of the online buzz marketing.